2021
DOI: 10.1093/eurheartj/ehab348
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection is associated with thoracic and abdominal aortic aneurysms: a prospective matched cohort study

Abstract: Aims Little is known about the prevalence of aortic aneurysms among people living with HIV (PLWH). We investigated whether HIV status is independently associated with having aortic aneurysms. Furthermore, we determined risk factors associated with aortic aneurysms in PLWH. Methods and results PLWH aged ≥40 years (n = 594) were recruited from the Copenhagen Comorbidity in HIV Infection study and matched for age and sex with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 43 publications
2
38
2
Order By: Relevance
“…Using the Danish definition of ascending aorta dilation by computed tomography of ≥4.5 cm to define aneurysm, the rate of ascending aortic aneurysm in that study was low at 2.4%. 11 Høgh et al found no significant associations between non‐HIV and HIV‐related disease‐severity risk factors and aortic aneurysms including nadir CD4 count and inflammatory biomarker levels. 11 In contrast to the Danish study, our cohort was racially diverse and older, with lower rates of HIV viral suppression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Danish definition of ascending aorta dilation by computed tomography of ≥4.5 cm to define aneurysm, the rate of ascending aortic aneurysm in that study was low at 2.4%. 11 Høgh et al found no significant associations between non‐HIV and HIV‐related disease‐severity risk factors and aortic aneurysms including nadir CD4 count and inflammatory biomarker levels. 11 In contrast to the Danish study, our cohort was racially diverse and older, with lower rates of HIV viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Høgh et al found no significant associations between non‐HIV and HIV‐related disease‐severity risk factors and aortic aneurysms including nadir CD4 count and inflammatory biomarker levels. 11 In contrast to the Danish study, our cohort was racially diverse and older, with lower rates of HIV viral suppression. Cardiac risk factor prevalence between the MWH and MWOH in our cohort was generally similar except for a higher rate of dyslipidemia and resultant statin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only one of the PWH with aortic aneurysm in this study were evaluated to need surgical procedure. The fact that in both these studies only a few cases of PWH, who were diagnosed with an aortic aneurysm, had surgery performed [13,34] could indicate that most of the aortic aneurysms were not of clinical significance. Complications for smaller aortic aneurysms occur infrequently [39] and severe cases of aortic aneurysms with potential complications among PWH seems to be rare as well.…”
Section: Discussionmentioning
confidence: 99%
“…As both clinical consequential aneurysms and ruptures are rare, studies that investigate the association between HIV infection and the risk of aneurysms or associated subarachnoid haemorrhages should be large-scale observational studies. However, previous evidence from case-series or crosssectional studies is hampered by small study sizes and lack of well matched comparison cohorts or investigated molecular or pathological mechanisms rather than risk [4][5][6]8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%